PERLINDUNGAN HUKUM BAGI DEBITUR ATAS PELAKSANAAN EKSEKUSI OLEH PERUSAHAAN LEASING TERHADAP JAMINAN FIDUSIA YANG DITARIK SECARA PAKSA - Herawati, Eti Herawati; Kencanawati, Erny; Hutomo, Putra (RIO LAW JURNAL, 2025)
n general, the execution of collateral objects causes disputes because the creditor wants the right to repay the debt on the collateral object, while the debtor is not willing to have the collateral object executed to pay off the debt. So sometimes in practice, creditors take the law into their own hands in the collateral execution process carried out by creditors as fiduciary recipients, to take over goods controlled by debtors without going through the correct legal procedures. This research discusses 1) How is the execution of fiduciary guarantees withdrawn by leasing companies by force? 2) What is the legal protection for debtors regarding the execution by leasing companies of fiduciary guarantees that are forcibly withdrawn? Constitutional Court Decision Number 18/PUU-XVII/2019 reduces the power of the executorial title of a fiduciary guarantee certificate which means that the ease of execution carried out by creditors cannot be carried out properly. This is not in line with the principles of droit de suite, droit de preference and para executie which are threatened with not being implemented as a result of the Constitutional Court's interpretation which states that the executorial power of a Fiduciary Guarantee Certificate has no legal force if there is no agreement on breach of contract and willingness to surrender the collateral object from the fiduciary guarantee provider (debtor). In the event of a default by the Debtor, the execution of the collateral object must be submitted to court first by the Creditor. If this is not done, the Debtor can file a lawsuit for an unlawful act against the Creditor's actions.Keywords :Fiduciary, Legal Protection, Guarantee Execution Debtors